Mantle oxidation state and its relationship to tectonic environment and fluid speciation. - Wood, B; Bryndzia, LT; Johnson, K (1990)
The earth's mantle is degassed along mid-ocean ridges, while rehydration and possibly recarbonaton occurs at subduction zones. These processes and the speciation of C-H-O fluids in the mantle are related to the oxidation state of mantle peridotite. Peridotite xenoliths from continental localities exhibit an oxygen fugacity (fo(2)) range from -1.5 to +1.5 log units relative to the FMQ (fayalite-magnetite-quartz) buffer. The lowest values are from zones of continental extension. Highly oxidized xenoliths (fo(2) greater than FMQ) come from regions of recent or acive subduction (for example, Ichinomegata, Japan), are commonly amphibole-bearing, and show trace element and isotopic evidence of fluid-rock interaction. Peridotites from ocean ridges are reduced and have an averae fo(2) of about -0.9 log units relative to FMQ, virtually coincident with values obtained from mid-ocean ridge basalt (MORB) glasses. These data are further evidence of the genetic link between MORB liquids and residual peridotite and indicate that the asthenosphere, although reducing, has CO(2) and H(2)O as its major fluid species. Incorporation of oxidized material from subduction zones into the continental lithosphere produces xenoliths that have both asthenospheric and subduction signatures. Fluids in the lithosphere are also dominated by CO(2) and H(2)O, and native C is generally unstable. Although the occurrence of native C (diamond) in deep-seated garnetiferous xenoliths and kimberlites does not require reducing conditions, calculations indicate that high Fe(3+) contents are stabilized in the garnet structure and that fo(2) deareases with increasing depth.